Portion perfection and Emotional Freedom Techniques to assist bariatric patients post surgery: A randomised control trial. Issue 6 (June 2020) - Stapleton, Peta; Clark, Amanda; Sabot, Debbie; Carter, Brett; Leech, Kelly
Abstract: Background: Although significant health improvements are indicated from weight-loss following bariatric surgery, many individuals are unable to lose weight or maintain their weight-loss. The current study aimed to assess whether post-surgery care comprising Emotional Freedom Techniques (EFT), an emerging energy psychology intervention, combined with a behaviour-based nutrition and portion control eating plan in an online self-guided delivery would aid weight-loss and maintenance in bariatric patients. Methods: A 6-month randomised controlled parallel-group trial. Participants ( N = 343; aged 21–69 years; BMI ≥30 kg/m 2 ) had undergone bariatric surgery (12 + months prior) and were randomly assigned to one of three treatment groups: Portion Perfection for Bariatric Patients (PPBP; n = 109), PPBP combined with an eight-week online self-paced EFT treatment ( n = 107), and a treatment as usual (TAU) control ( n = 127). Participants completed measures of BMI, emotional eating, uncontrolled eating, food cravings, and self-esteem at 8-week post-treatment ( n = 158) and 6-month follow-up ( n = 109). Results: Mixed-design analyses of variances were conducted to examine the effect of the interventions on outcome measures (pre-intervention, 8-week post-intervention, and 6-month follow-up). Emotional eating decreased significantly from pre-intervention to post-intervention for the PPBP and PPBP with EFT groups, and at 6-month follow-up for the TAU group only. There were no statistically significant between-group differences in other outcome variables. However, at 6-months the PPBP with EFT group experienced the greatest improvements in emotional eating (-16.33%), uncontrolled eating (-9.36%), and self-esteem (+4.43%), compared to PPBP only or TAU. Conclusion: The effect of EFT combined with the eating plan on psychological variables was largely inconsistent with prior research and discussion of how this may be optimised in future trials is discussed. Clinical trial registration: ACTRN12616001257459. Abstract : Psychology; Health Psychology; Mental Health; Psychological Disorders; Well-Being; bariatric surgery; portion perfection; Emotional Freedom Techniques (EFT); emotional eating; uncontrolled eating; Self-esteem